Realization and representation of Nepali laryngeal contrasts: Voiced aspirates and laryngeal realism. (March 2019) - Schwarz, Martha; Sonderegger, Morgan; Goad, Heather
Highlights: Laryngeal realism extends to language with 4-way laryngeal contrast with minimal issue. Acoustics of Nepali voiced aspirates supports representation with [voice], [spread]. Diagnostics of feature specification show [voice] contrast stronger than [spread]. Abstract: Theories of laryngeal realism argue for a tight correspondence between a segment's phonetic cues and the (laryngeal) phonological features that represent it. As such, the 'p'/'b' contrast in French, expressed phonetically by vocal fold vibration during the stop closure, is represented by a [voice] feature while the 'p'/'b' contrast in English, expressed phonetically by contrasting long and short lag VOT, is represented by a [spread] feature. Laryngeal realist literature focuses on whether a given segment is best represented by [voice] or [spread], and proposes a set of criteria and tests by which to diagnose the representation. In this study we push laryngeal realist theory in a new direction – to segments proposed to be specified for both [voice] and [spread] features – a combination which poses challenges to the current diagnostics. To do so, we analyze acoustic data from Nepali, an Indic (a.k.a. Indo-Aryan) language with a single class of stops described as both voiced and aspirated. We apply the same criteria and diagnostics used in laryngeal realism. We find support for the proposed representation, with a caveat that the [voice] feature appears 'stronger' than [spread].